Dual antibiotherapy of tuberculosis mediated by inhalable locust bean gum microparticles - Rodrigues, Susana (2019)
Despite the existence of effective oral therapy, tuberculosis remains a deadly pathology, namely because of bacterial resistance and incompliance with treatments. Establishing alternative therapeutic approaches is urgently needed and inhalable therapy has a great potential in this regard. As pathogenic bacteria are hosted by alveolar macrophages, the co-localisation of antitubercular drugs and pathogens is thus potentiated by this strategy. This work proposes inhalable therapy of pulmonary tuberculosis mediated by a single locust bean gum (LBG) formulation of microparticles associating both isoniazid and rifabutin, complying with requisites of the World Health Organisation of combined therapy. Microparticles were produced by spray-drying, at LBG/INH/RFB mass ratio of 10/1/0.5. The aerodynamic characterisation of microparticles revealed emitted doses of more than 90% and fine particle fraction of 38%, thus indicating the adequacy of the system to reach the respiratory lung area, thus partially the alveolar region. Cytotoxicity results indicate moderate toxicity (cell viability around 60%), with a concentration-dependent effect. Additionally, rat alveolar macrophages evidenced preferential capture of LBG microparticles, possibly due to chemical composition comprising mannose and galactose units that are specifically recognised by macrophage surface receptors. (C) 2017 Elsevier B.V. All rights reserved.